Surfactants in agrochemicals - Tadros, Th. F. (New York : M. Dekker, 1995)
Highlighting the physical chemistry of surfactant solutions, this authoritative, single-source reference/text details a fundamental method of selecting surfactants for agrochemical formulations - delineating how surfactants enhance the biological efficacy of agrochemicals. Summarizing the unique properties of surfactants that have a major influence on the performance of an agrochemical, Surfactants in Agrochemicals discusses the micellization of surfactant solutions ... covers the adsorption of surfactants and polymers at the air/liquid, liquid/liquid, and solid/liquid interfaces ... explores the preparation and stabilization of emulsions ... analyzes suspension concentrates ... examines the advantages of using microemulsions instead of emulsions in the agrochemical industry ... describes the impaction, adhesion, and retention of surfactants in droplet formation ... investigates the role of surfactants in the transport of agrochemicals to the site of action ... and more.
Providing more than 240 up-to-date literature citations and over 260 helpful tables, equations, and drawings, Surfactants in Agrochemicals is a valuable reference for physical, surface, and colloid chemists; biochemists; microbiologists; agronomists; and research and development personnel in the pesticide and fertilizer industries; and an essential text for upper-level undergraduate and graduate students enrolled in chemistry and chemical engineering programs.
1. General Introduction -- 2. Physical Chemistry of Surfactant Solutions -- 3. Adsorption of Surfactants and Polymers at the Air/Liquid, Liquid/Liquid, and Solid/Liquid Interfaces -- 4. Emulsifiable Concentrates -- 5. Emulsions -- 6. Suspension Concentrates -- 7. Microemulsions -- 8. Role of Surfactants in the Transfer and Performance of Agrochemicals.
Includes bibliographical references (pages 249-259) and index.
Keywords: Surface-active agents; Agricultural chemicals -- Adjuvants